Quality of life among undergraduate university students during COVID-19 movement control order in Sarawak - Whye Lian, Cheah; Law, Leh Shii; Teh, Keng Hoong; Kam, Su Ling; Voon, Grace Ern Hu; Lim, Han Yong; Nuhes Seelan, Shashi Kumar (Wiley-VCH GmbH, 2021)
Background and Aims: The aim of this study was to examine the QoL and health satisfaction of undergraduate university students in Sarawak during MCO and its association with socio-demographic profiles.